2013
DOI: 10.1111/ahg.12027
|View full text |Cite
|
Sign up to set email alerts
|

Post-Genome-Wide Association Study Challenges for Lipid Traits: Describing Age as a Modifier of Gene-Lipid Associations in the Population Architecture Using Genomics and Epidemiology (PAGE) Study

Abstract: Summary Numerous common genetic variants that influence plasma high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) distributions have been identified via genome-wide association studies (GWAS). However, whether or not these associations are age dependent has largely been overlooked. We conducted an association study and meta-analysis in more than 22,000 European Americans between 49 previously identified GWAS variants and the three lipid traits, stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We also identified ten known lipid lociwith interactions that lacked even suggestive evidence without interactions, showing the impact that age-dependent effects may have on the consistency of results across populations. Other investigations have reported gene-age interactions in three of our known QTLs [6, 11, 13], lending some credibility to the results from our modeling method. Known loci on chromosomes 1p33, 2q14.1, and 6p22.3 contained SNPs (in PCSK9 [11], INSIG2 [13], and an intergenic region[6], respectively)that yielded nominal evidence (p-value<0.05) of age interactions in prior lipid investigations.…”
Section: Discussionsupporting
confidence: 75%
“…We also identified ten known lipid lociwith interactions that lacked even suggestive evidence without interactions, showing the impact that age-dependent effects may have on the consistency of results across populations. Other investigations have reported gene-age interactions in three of our known QTLs [6, 11, 13], lending some credibility to the results from our modeling method. Known loci on chromosomes 1p33, 2q14.1, and 6p22.3 contained SNPs (in PCSK9 [11], INSIG2 [13], and an intergenic region[6], respectively)that yielded nominal evidence (p-value<0.05) of age interactions in prior lipid investigations.…”
Section: Discussionsupporting
confidence: 75%
“…Also, conventionally increasing sample sizes without correction for population substructures may raise heterogeneity within populations ( 72 ), likely concealing the SNPs that affect particular subgroups. Future specific studies should counter the widely held assumption of unconditional risk alleles of complex traits and focus on the importance of studying more homogenous subgroups to, for example, investigate the age-dependent effect of genetic variants ( 73 , 74 ). Here, while further exploring the pleiotropic effect of IL-6-related variants, we identified phenotypes differentially regulated by diverse variants in the 1q21 locus.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] In earlier analyses in the GLACIER Study, we showed that whereas some of the 157 loci robustly associated with cross-sectional lipid concentrations 2,3 also convey robust effects on long-term changes in lipids, most loci do not. 8 Thus, discovering loci related to long-term changes in blood lipids, and not merely focusing on variants that are known to bear cross-sectional associations, 10 might be informative for the early identification of persons at high risk of atherosclerotic heart disease; such studies might also yield leads for targeted prevention, as loci that predict changes with age might do so owing to interactions with ageing-related risk factors or cumulative environmental exposures. 7…”
Section: Introductionmentioning
confidence: 99%